1991
DOI: 10.1111/j.1476-5381.1991.tb12540.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ channel activation and membrane depolarization mediated by Cl channels in response to noradrenaline in vascular myocytes

Abstract: I The effects of noradrenaline (NA) were studied on vascular smooth muscle cells isolated from rat portal vein. 2 Two types of single-Ca2+ channel currents with conductances of 17pS and 8pS were obtained in cell-attached configuration. Bath application of NA increased the open probability of both channels during depolarizing pulses without a change of background membrane conductance. However, NA did not open Ca2 + channels when the membrane patch potential was held at -50mV, which is about the resting potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…Other investigators have suggested that certain agonists activate chloride channels in vascular smooth muscle. For instance, noradrenaline-induced contractions of rat portal vein are inhibited by 9-anthracene chloride (Pacaud et al 1991), a blocker of various types of chloride channels (Large & Wang, 1996). Endothelin-, noradrenaline-, and angiotensin II-induced constrictions of renal arterioles are inhibited by IAA_94 (Carmines, 1995;Takenaka, Kanno, Kitamura, Hayashi, Suzuki & Saruta, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have suggested that certain agonists activate chloride channels in vascular smooth muscle. For instance, noradrenaline-induced contractions of rat portal vein are inhibited by 9-anthracene chloride (Pacaud et al 1991), a blocker of various types of chloride channels (Large & Wang, 1996). Endothelin-, noradrenaline-, and angiotensin II-induced constrictions of renal arterioles are inhibited by IAA_94 (Carmines, 1995;Takenaka, Kanno, Kitamura, Hayashi, Suzuki & Saruta, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Since this tonic contraction was generated in the presence of methoxyverapamil, it can be concluded that the inhibitory effect of UR-8225 and levcromakalim on K+ conductance does not require the entry of Ca2" through dihydropyridine-sensitive channels (Kreye & Weston, 1986). The inhibitory effect on noradrenaline-induced tonic contractions can be explained because noradrenaline increases open state-probability of single voltage-activated Ca2" channels (Nelson et al, 1988;Pacaud et al, 1991), whereas K+ channel openers oppose this action by hyperpolarizing the membrane potential (Hamilton et al, 1986;Bray et al, 1991). Other possible explanations are that the hyperpolarization induced by UR-8225 and levcromakalim may inhibit the ability of depleted intracellular Ca2" stores to refill after Ca2" release has occurred and/or the synthesis of inositol 1,4,5-trisphosphate (IP3)-induced by noradrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…The MIA-adrenoceptor subtype has been shown to gate Ca2" influx, sometimes through L-type Ca2+ channels but it has also been reported that the a 1A-adrenoceptor subtype could stimulate the formation of inositol phosphates (Han et al, 1990). In portal vein smooth muscle, the sequence of events induced by noradrenaline can be summarized as follows: (i) noradrenaline releases intracellular Ca2+ stores through InsP3 production; (ii) the calcium released opens chloride channels producing outward chloride current and membrane depolarization (Byrne & Large, 1988); (iii) this depolarization produces Ca2+ entry through voltagedependent Ca2+ channels; (iv) the open probability of Ca2+ channels is enhanced by noradrenaline (Pacaud et al, 1991). As activation of the alL-adrenoceptor subtype alone is unable to elicit contraction, these results suggest that both (XIL-and OClN-adrenoceptors mediate the noradrenaline-induced contraction in physiological conditions.…”
Section: High-and Low-affinity Binding Sites For [3h]-prazosin In Vasmentioning
confidence: 99%